Indirect Agent Interaction within an Approach for a Robust Transport Control in Dynamic and Multimodal Logistics Networks - Jung, Heiko; Weissbach, Samuel; Kappler, Jochen (Electronic Communications of the EASST, 2011)
This paper outlines the motivation for a robust transport control in dynamic and multimodal logistics networks. For the accomplishment of this overall goal our current research effort intends to contribute by the development of a decentraland heterarchical organised control approach, which is implemented as a multi-agent system. Thereby, a new mechanism combining indirect and direct interactionbetween transport requesting and offering agents will be studied. This paper presents the blueprint of the indirect interaction, which is realised by the incorporation of a coordination artifact. This artifact represents a logistics network and is a workspace commonly shared by all agents.